The application of tanazul and its shariah issues in equity based sukuk - Mohd Noor, Azman; Haron, Muhamad Nasir; Mohammad, Sri Zuraihan (ISTAC, 2015)
Nowadays, there are number of product innovations in Islamic capital market instruments particularly in Sukuk using the equity based contract; musharakah, mudharabah and wakalah bi al istithmar. In Islamic parameter of these contracts, there shall be no determination of return or possible arrangement that may lead to guaranteeing the return of any partners in musharakah and mudarabah. Conversely, conventional bond usually offers a fixed income determination for their bond structures and issuance. Yet, this raises issue as to whether the sukuk equity based structure may have the same implication. Then, this is where the tanazul may play its role to give effect in sukuk structuring using musharakah, mudarabah and wakalah bi al istithmar contracts to offer a similar feature of fixed income instrument. This paper attempts to ascertain the status of tanazul in equity based sukuk from Shariah perspective. The paper will analyze the use of concept tanazul in sukuk structures and its implications on the validity of the equity based sukuk transactions.